KAJIAN PENAMBAHAN Effective Microorganisms (EM4) PADA PROSES DEKOMPOSISI LIMBAH PADAT INDUSTRI KERTAS - Nana Dyah Siswati; Herwindo Theodorus; Puguh Wahyu Eko S (Universitas Tribhuwana Tunggadewi, 2009)
The solid waste at PT Kertas Leces Probolinggo has not been properly handled as it is just ended in the waste landfill. Composting is a method to process the solid waste with a high organic content. In that process the organic agent is degraded by micro organism that driving to stabilize the organic content. In this research effective micro organism (EM4) was used as a disspator organism in some range of concentrate (2,4,6,8,10) (%) v/b and observed in 5,10,15,20,25 days composting time. The best result was reached on the concentrate of 2 % EM4 & 25 days decomposting time, with the rasio C/N = 14,11 (most land has rasio indicator C/N closed to 10) comparing to the previous grade = 33,24.